Comparison of the osseointegration of implants placed in areas grafted with HA/TCP and native bone - Lima, Julia Raulino (2022)
This study evaluated the osseointegration of implants in areas grafted with biphasic ceramic based on hydroxyapatite/β-tricalcium phosphate (HA/TCP) and in native bone (NB). Twenty-eight rats were randomly assigned into two groups of 14 animals each: HA/TCP group: implants installed in areas grafted with HA/TCP and NB group: implants installed in areas of native bone. Bone defects were made in both tibiae of the rats belonging to the HA/TCP group and then filled with this bone substitute. After 60 days, the rats were submitted to surgical procedures for implant placement in grafted areas in both tibiae in the HA/TCP group while the implants were installed directly in native bone in the NB group. The animals were euthanized 15 and 45 days, respectively, after the implant placement. Biomechanical (removal torque), microtomographic (volume of mineralized tissues around the implants), and histomorphometric (Bone-Implant contact—%BIC and bone area between the implant threads—%BBT) analyzes were conducted to assess the osseointegration process. The HA/TCP group showed lower values of removal torque, volume of mineralized tissue around the implants, lower %BIC, and %BBT compared to the NB group in both experimental periods. Osseointegration of implants placed in grafted areas with HA/TCP was lower compared to the osseointegration observed in native bone areas.